Reduction of Indoor Air Temperature by Using POFA Foamed Concrete Block - Awang, Hanizam (International Journal of Integrated Engineering, 2019)
People use air conditioning (AC) systems to enhance the indoor thermal comfort of buildings, especially those that are located in tropical countries such as Malaysia. Despite reducing the indoor air temperature, AC systems consume a high amount of energy and produce negative effects on the urban thermal environment. The carbon dioxide released by AC systems also trigger a greenhouse effect, which in turn can thicken the thermal blanket of the earth. Lightweight foamed concrete blocks have been recently highlighted for their potential use in addressing the harmful effects of AC systems. Therefore, this study examines how POFA foamed concrete blocks can reduce the indoor air temperature of buildings and other structures. The results show that these blocks reduce the indoor air temperature to levels that are lower than the outdoor temperature for approximately 10 hours a day. The reduction in temperature can reach as high as 5.69 ÂºC during peak periods. Given their ability to reduce the indoor air temperature, POFA foamed concrete blocks can also reduce the energy consumption of AC systems with their long-term use.